How Mixed Farming Innovations are Shaping the Livelihood of Rural Bangladesh - Haque, Abdul; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2025)
The economy of Bangladesh is largely dependent on agriculture, and most of the people are dependent on it directly and indirectly. Agriculture remains vital for GDP (11.3%), employment, and food security. But nowadays, this sector faces several challenges, such as climate change, labor shortages, increasing input costs, and price volatility of produced products. Low income and unstable earnings from farming due to seasonal requirements push many workers to seek better-paying jobs outside agriculture. Garments, construction, transport, and services offer more stable, better-paying jobs, attracting rural youth.